The Process of Innovation Diffusion and Adoption of Innovations in the Business Modelling for Travel Companies - KARMANOV, Mikhail Vladimirovich; KISELEVA, Irina Anatolievna; KUZNETSOV, Vladimir Ivanovich; ZAVRAZHIN, Anatoly Vladimirovich; SHUBINA, Irina Vladimirovna (Journal of Environmental Management and Tourism, 2020)
The international practice among leading companies indicates that there is no successful development and sound company performance improvement, particularly, in tourism, without a proper strategy as a complex of measures tailored to achieve the set goal. Technology development in tourism represents a leading trend of the global economy, shaped by the restructuring of modern society. The Russian Federation public policy has a clear set economic goal in the tourism sector, which is to transform tourism as a competitive, innovative stable and profitable sector of national business. Tourism is characterised by a complicated relationship system between the providers and consumers of services, between travel companies and their competitors and between business partners. A travel company's activities in the market include finding a niche; tourism product development; determining the scope of services; refinement of pricing; expansion of promotion activities, research; ensuring investment; cooperation with other companies; government relations. Today, various methods and models are intensely adopted in the development of business management systems in tourism, which reflects the increased competitiveness of products in the tourism market. The paper discusses development models for travel companies, methods for solving optimisation problems of the regional territorial arrangement of tourism and hotel business and establishes the influence of external environment factors over the creation of a hotel operation.